2017
DOI: 10.1016/j.jallcom.2017.03.063
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive behavior of Al2O3np/Al7075 composites with a high solid fraction for thixoforming

Abstract: The thixotropic compression tests of nano-Al 2 O 3 (Al 2 O 3np) /Al7075 composites with different particle sizes and contents and containing a high fraction of solid, were conducted under conditions of 560-590 °C and 0.01-5 s-1 , and the microstructures were observed. A visco-plastic constitutive model of nanoparticle reinforced composites for thixoforming was proposed, considering the coupling effects of strain, strain rate, deformation temperature and liquid fraction and presence of nanoparticles, to describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Quantitative analysis of the micrographs of the specimens in the semi-solid state were carried out using Image-Pro Plus software (Media Cybernetics Company, Sliver Spring, MD, USA) and the statistical results of solid fraction and shape factor were determined by three OM images. The shape factor of solid particles was calculated by the following equation [22]:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative analysis of the micrographs of the specimens in the semi-solid state were carried out using Image-Pro Plus software (Media Cybernetics Company, Sliver Spring, MD, USA) and the statistical results of solid fraction and shape factor were determined by three OM images. The shape factor of solid particles was calculated by the following equation [22]:…”
Section: Methodsmentioning
confidence: 99%
“…The solid volume fraction varied in the range from 0.69 to 0.81 and increased with the prolonging isothermal soaking time from 5 min to 30 min. It was revealed that the semi-solid slurry with a high solid fraction between 0.75 and 0.8 had the better thixotropic behavior [6,22]. Moreover, the forming defects such as porosity, inclusions or shrinkage could be visibly prevented in the high solid fraction semi-solid feedstock during the forming process.…”
Section: Shape Factor Average Solid Grain Size and Solid Fraction Ofmentioning
confidence: 99%
“…The liquid fraction was measured mainly by the liquid films between solid particles by the metallographic method. In this work, the average grain size (D eq ) of solid particles and the shape factor (°C) were calculated by the following equations: [29][30][31]…”
Section: Microstructure Characterizationmentioning
confidence: 99%
“…Aluminum alloy matrix composites are widely used in the automobile and communication industries, as well as in military and aerospace series due to their high specific strengths, specific stiffnesses, specific moduli, and low coefficients of linear expansion properties [1]. Aluminum alloy matrix composites have recently developed into high-profile emerging materials [2,3].…”
Section: Introductionmentioning
confidence: 99%